Essays on the Design of Contracts and Markets for Power System Flexibility - Luis R. Boscán F. (Copenhagen Business School (CBS), 2016)
This PhD thesis consists of five essays on the economics of Power System Flexibility, a topic that has traditionally been addressed from a technical perspective by engineers, system planners, electricity industry stakeholders and energy policymakers interested in the integration of Variable Renewable Energy. While significant progress has been made in the understanding and characterization of exibility, its economic properties and the required incentives to provide it have not been suficiently analyzed. The present work aims at filling this gap.
hdl:10398/9367
Keywords: 650